Unlocking Competitive Talent: a Case Study on the Improvement of Leadership Development Through a Learning Journey (Catalyser Program) at PT Pertamina - el Mubarak, Muhammad Fahmi; Lantu, Donald Crestofel (Jurnal Locus Penelitian dan Pengabdian, 2025)
This study critically evaluates the Catalyser Leadership Development Program implemented by PT.Pertamina (Persero), Indonesia's state-owned energy giant, against the backdrop of accelerating global energy transitions and organizational restructuring. Through in-depth interviews with 3 key stakeholders (program alumni, non alumni, and HR Designer), the research reveals a paradox: while the program successfully employs blended learning methodologies aligned with 70:20:10 principles (Lombardo & Eichinger, 1996), critical disconnects emerge in sustaining leadership capabilities post-program. The study makes a significant contribution by proposing an enhanced "Catalyser 2.0" framework, updated based on stakeholder feedback and grounded in adaptive leadership principles. The study also offers policy recommendations that emphasize urgency of formulating a comprehensive and sustainable talent management strategy.